Improvements in Key Cardiopulmonary Exercise Testing Variables Following Cardiac Rehabilitation in Patients With Coronary Artery Disease. Issue 5 (September 2018) - Popovic, Dejana; Kumar, Nikhil; Chaudhry, Sundeep; Bagai, Akshay; Arena, Ross; Kumar, Naresh
Abstract : Purpose: Improvements in cardiorespiratory fitness ( O2peak ) post-cardiac rehabilitation (post-CR) are used to gauge therapeutic efficacy. The aim of the present study was to assess the effect of supervised CR on other cardiopulmonary exercise testing (CPX) variables, specifically those that reflect ventilatory efficiency and O2 changes in relation to changes in work rate (WR). Methods: Patients (n = 142; mean age 63 ± 9 y; 23% female) with coronary artery disease (CAD) participated in supervised CR for 3 to 6 mo completing 60 ± 17 sessions (range: 32-96 sessions), with intensity derived from the baseline CPX. CPX was completed at baseline and post-CR on a cycle ergometer. The minimum heart rate (HR) during cycling was set 5 to 10 beats/min above the HR at ventilatory anaerobic threshold (VAT) while the maximum HR remained below the ischemic threshold observed during CPX, and this intensity was maintained for 25 min. O2peak, peak O2 pulse, the minute ventilation/carbon dioxide production ( E / CO2 ) slope, the oxygen uptake efficiency slope (OUES), and the Δ O2 /ΔWR slope were determined at baseline and post-CR. Results: Following CR, there were significant improvements (all P < .001) in O2peak (17.7 ± 4.7 mL/kg/min vs 20.9 ± 5.4 mL/kg/min), peak O2 pulse (11.6 ± 3.2 mL/beat vs 13.4 ± 3.6 mL/beat), E / CO2 slope (28.4 ± 5.3 vs 27.5 ± 4.7), OUES (1.8 ± 0.5 vs 2.0 ± 0.6), and Δ O2 /ΔWR slope (9.1 ± 1.2 mL/min/W vs 9.6 ± 1.1 mL/min/W). Conclusion: Key markers of ventilatory efficiency and O2 kinetics during CPX significantly improve following CR. Expanding the list of variables assessed via CPX may provide better resolution in validation of CR therapeutic efficacy in patients with CAD. Abstract : The present study assessed the effect of cardiac rehabilitation (CR) on cardiopulmonary exercise testing (CPX) variables other than O2peak in patients with coronary artery disease. Ventilatory efficiency and the kinetics of O2 during CPX significantly improve following CR, providing better resolution of therapeutic efficacy of CR.